Studies of solvent effect on the conductivity of 2-mercaptopyridine-doped solid polymer blend electrolytes and its application in dye-sensitized solar cells - Theerthagiri, J.; Senthil, R.A.; Buraidah, Mohd Hamdi; Madhavan, J.; Arof, Abdul Kariem (Wiley, 2015)
Solvents and electrolytes play an important role in the fabrication of dye-sensitized solar cells (DSSCs). We have studied the poly(ethylene oxide)-poly(methyl methacrylate)-KI-I2 (PEO-PMMA-KI-I2) polymer blend electrolytes prepared with different wt % of the 2-mercaptopyridine by solution casting method. The polymer electrolyte films were characterized by the FTIR, X-ray diffraction, electrochemical impedance and dielectric studies. FTIR spectra revealed complex formation between the PEO-PMMA-KI-I2 and 2-mercaptopyrindine. Ionic conductivity data revealed that 30% 2-mercaptopyridine-doped PEO-PMMA-KI-I2 electrolyte can show higher conductivity (1.55 × 10-5 S cm-1) than the other compositions (20, 40, and 50%). The effect of solvent on the conductivity and dielectric of solid polymer electrolytes was studied for the best composition (30% 2-mercaptopyridine-doped PEO-PMMA-KI-I2) electrolyte using various organic solvents such as acetonitrile, N,N-dimethylformamide, 2-butanone, chlorobenzene, dimethylsulfoxide, and isopropanol. We found that ac-conductivity and dielectric constant are higher for the polymer electrolytes processed from N,N-dimethylformamide. This observation revealed that the conductivity of the solid polymer electrolytes is dependent on the solvent used for processing and the dielectric constant of the film. The photo-conversion efficiency of dye-sensitized solar cells fabricated using the optimized polymer electrolytes was 3.0% under an illumination of 100 mW cm-2. The study suggests that N,N-dimethylformamide is a good solvent for the polymer electrolyte processing due to higher ac-conductivity beneficial for the electrochemical device applications.